1976
DOI: 10.1111/j.1755-3768.1976.tb01791.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Length of Wear of Contact Lenses on Corneal Sensitivity

Abstract: Corneal touch thresholds (CTT) were determined once in the morning before inserting contact lenses then after 4, 8 and 12 h of continuous wear. Two groups of subjects participated in this study; 12 persons wearing hard contact lenses and 15 wearing soft contact lenses. All subjects were perfectly adapted to their contact lenses and had worn them for not less than three months. It was found that hard contact lenses caused a progressive diminution of corneal sensitivity. After 12 h corneal sensitivity was, on av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1
2

Year Published

1978
1978
2013
2013

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 16 publications
0
25
1
2
Order By: Relevance
“…Millodot observed a reduction in corneal sensitivity with both hard and soft CL wear, and a more pronounced reduction in sensitivity with hard CL wear [33,34]. With hard CL wear, a significant recovery of corneal sensitivity was observed within the first hour after lenses were removed, however, complete recovery took longer and was also related to length of CL wear [35,36]. In a more recent study involving silicone hydrogel lenses, Situ et al found that a decrease in corneal sensitivity occurred after only 2 weeks of wear, suggesting that hypoxia is not the sole explanation for decreased corneal sensation [37].…”
Section: Discussionmentioning
confidence: 99%
“…Millodot observed a reduction in corneal sensitivity with both hard and soft CL wear, and a more pronounced reduction in sensitivity with hard CL wear [33,34]. With hard CL wear, a significant recovery of corneal sensitivity was observed within the first hour after lenses were removed, however, complete recovery took longer and was also related to length of CL wear [35,36]. In a more recent study involving silicone hydrogel lenses, Situ et al found that a decrease in corneal sensitivity occurred after only 2 weeks of wear, suggesting that hypoxia is not the sole explanation for decreased corneal sensation [37].…”
Section: Discussionmentioning
confidence: 99%
“…response in the asymptomatic lens wearers compared with those not wearing lenses might be because of the decreased sensitivity of the ocular surface. 40 Secretion by the lacrimal glands is stimulated by the trigeminal nerve that innervates the ocular surface, adnexa, and nasal mucosa. [41][42][43] Yen et al 44 found that both ocular surface sensation and tear secretion decreased after temporary punctal occlusion, especially in normal subjects with both upper and lower puncta occluded.…”
Section: Discussionmentioning
confidence: 99%
“…4 It is well known that contact lens wear causes loss of corneal sensation regardless of the lens material and wearing modality. [5][6][7][8][9] Clinicians have observed that contact lens wear can increase the corneal touch threshold to values that are so high that some patients do not experience any pain or discomfort even if the cornea is abraded. 10 In addition, several reports have suggested that the loss of corneal sensation resulting from wearing contact lenses increases the risk of infection.…”
Section: Introductionmentioning
confidence: 99%